2006
DOI: 10.1084/jem.20060468
|View full text |Cite
|
Sign up to set email alerts
|

Expression of interleukin (IL)-2 and IL-7 receptors discriminates between human regulatory and activated T cells

Abstract: Abnormalities in CD4+CD25+Foxp3+ regulatory T (T reg) cells have been implicated in susceptibility to allergic, autoimmune, and immunoinflammatory conditions. However, phenotypic and functional assessment of human T reg cells has been hampered by difficulty in distinguishing between CD25-expressing activated and regulatory T cells. Here, we show that expression of CD127, the α chain of the interleukin-7 receptor, allows an unambiguous flow cytometry–based distinction to be made between CD127lo T reg cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

78
1,118
8
24

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,353 publications
(1,235 citation statements)
references
References 30 publications
78
1,118
8
24
Order By: Relevance
“…1A. For CD127 À Treg cell isolation, the gating strategy suggested by Seddiki et al [19] and Liu et al [20] was used, whereby CD4 1 CD25 1 cells with FSc/SSc characteristics of lymphocytes and with low CD127 expression level were sorted (Fig. 1B) Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A. For CD127 À Treg cell isolation, the gating strategy suggested by Seddiki et al [19] and Liu et al [20] was used, whereby CD4 1 CD25 1 cells with FSc/SSc characteristics of lymphocytes and with low CD127 expression level were sorted (Fig. 1B) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we aimed to clarify these issues with the help of two recent advances in the field: First, we recently described that natural Treg differ from other T-cell populations in their DNA methylation status of a defined region within the FOXP3 locus termed Treg-specific demethylation region (TSDR): Demethylation of this region is exclusively observed in natural Treg, but neither in activated Tconv cells nor in TGF-b-induced Treg [17,18]. Second, the groups of Fazekas de Saint Groth and Bluestone reported that human CD4 1 CD25 1 Treg can be distinguished from activated (and thus also CD25 1 ) Tconv cells by their different surface expression levels of CD127 (IL-7 receptor a-chain, IL-7Ra): whereas activated Tconv cells are strongly positive for CD127, Treg show only low or no expression of this marker [19,20]. Thus, sorting of CD4 1 CD25 1 CD127 low/neg T cells (CD127 À Treg) should minimize contamination of the starting population with Tconv cells and this increased purity should result in homogeneous Treg cell products after expansion.…”
Section: Introductionmentioning
confidence: 99%
“…This definition of T reg has been well established in samples from healthy controls. 16,17 We validated correct T reg identification within CD3-positive/CD4-positive/CD25-positive/CD127-negative cells in a subgroup of patients with CLL by detecting high intracellular expression levels of FoxP3 and the ability to suppress Tcell proliferation (Fig. 1).…”
Section: Definition and Stability Of T Regs In Cllmentioning
confidence: 95%
“…Following recent reports that suggested measuring the expression of CD127 (22) (down-regulated by FoxP3) and C45RA (23,24) as adjuncts to Treg cell identification, we evaluated the correlation between expression of these markers and expression of CD25 high and FoxP3 cells. We found good correlations between these different methods of identifying Treg cells in our study population (data not shown).…”
Section: Decreasedmentioning
confidence: 99%